Arsenic concentrations, diversity and co-occurrence patterns of bacterial and fungal communities in the feces of mice under sub-chronic arsenic exposure through food. (May 2020) - Wang, Jiating; Hu, Wei; Yang, Huilin; Chen, Fubin; Shu, Yanling; Zhang, Guiwei; Liu, Jizhen; Liu, Yungang; Li, Huawen; Guo, Lianxian
Highlights: Subchronic arsenic exposure via food changes the gut microbiome. Feces might be the main excreting pathway for arsenic from food exposure. The toxicity of arsenic in staples should be comprehensively evaluated. Gut microbiome interaction might be disturbed by arsenic. Arsenic exposure would disturb carbohydrates, lipid, and amino acids metabolism of gut bacteria. Abstract: Background: Arsenic, a global pollutant and a threshold-free primary carcinogen, can accumulate in rice. Previous studies have focused on arsenic poisoning in drinking water and the effects on gut microbes. The research on arseniasis through food, which involves the bio-transformation of arsenic, and the related changes in gut microbiome is insufficient. Method: Mice were exposed from animal feed prepared with four arsenic species (iAs III, iAs V, MMA, and DMA) at a dose of 30 mg/kg according to the arsenic species proportion in rice for 30 days and 60 days. The levels of total arsenic (tAs) and arsenic species in mice feces and urine samples were determined using ICP-MS and HPLC-ICP-MS, respectively. 16S rRNA and ITS gene sequencing were conducted on microbial DNA extracted from the feces samples. Results: At 30 days and 60 days exposure, the tAs levels excreted from urine were 0.0092 and 0.0093 mg/day, and tAs levels in feces were 0.0441 and 0.0409 mg/day, respectively. We found significant differences in arsenic species distribution in urine and feces ( p  < 0.05). In urine, the predominant arsenic species were iAs III (23% and 14%, respectively), DMA (55% and 70%, respectively), and uAs (unknown arsenic, 14% and 10%, respectively). In feces, the proportion of major arsenic species (iAs V, 26% and 21%; iAs III, 16% and 15%; MMA, 14% and 14%; DMA, 19% and 19%; and uAs, 22% and 29%, respectively) were evenly distributed. Microbiological analysis (MRPP test, α- and β-diversities) showed that diversity of gut bacteria was significantly related to arsenic exposure through food, but diversity of gut fungi is less affected. Manhattan plot and LEfSe analysis showed that arsenic exposure significantly changes microbial taxa, which might be directly associated with arsenic metabolism and diseases mediated by arsenic exposure, such as Deltaproteobacteria, Polynucleobacter, Saccharomyces, Candida, Amanitaceae, and Fusarium . Network analysis was used to identify the changing hub taxa in feces along with arsenic exposure. Function predicting analysis indicated that arsenic exposure might also significantly increase differential metabolic pathways and would disturb carbohydrates, lipid, and amino acids metabolism of gut bacteria. Conclusions: The results demonstrate that subchronic arsenic exposure via food significantly changes the gut microbiome, and the toxicity of arsenic in food, especially in staples, should be comprehensively evaluated in terms of the disturbance of microbiome, and feces might be the main pathway through which arsenic from food exposure is excreted and bio-transformed, providing a new insight into the investigation of bio-detoxification for arseniasis.